2020
DOI: 10.5851/kosfa.2019.e97
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Fiber Typing in Bovine and Porcine Skeletal Muscles Using Immunofluorescence with Monoclonal Antibodies Specific to Myosin Heavy Chain Isoforms

Abstract: The aim of this study was to optimize staining procedures for muscle fiber typing efficiently and rapidly in bovine and porcine skeletal muscles, such as longissimus thoracis, psoas major, semimembranosus, and semitendinosus muscles. The commercially available monoclonal anti-myosin heavy chain (MHC) antibodies and fluorescent dyeconjugated secondary antibodies were applied to immunofluorescence histology. Two different procedures, such as cocktail and serial staining, were adopted to immunofluorescence analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
(42 reference statements)
3
21
0
Order By: Relevance
“…Our results, regardless of cut groups, corroborated with the previous observations. Additionally, the muscle fiber compositions in M-Vertical and F-Vertical groups were found to be similar to those reported by previous studies that demonstrated that glycolytic fiber (IIX or IIB) content was higher than the oxidative fiber (I or IIA) content in pork loin [19,[24][25][26]. Notably, the F-Parallel group exhibited a nearly double type I and IIA fiber content and nearly half of type IIB fiber content when compared to the M-Vertical and F-Vertical groups.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our results, regardless of cut groups, corroborated with the previous observations. Additionally, the muscle fiber compositions in M-Vertical and F-Vertical groups were found to be similar to those reported by previous studies that demonstrated that glycolytic fiber (IIX or IIB) content was higher than the oxidative fiber (I or IIA) content in pork loin [19,[24][25][26]. Notably, the F-Parallel group exhibited a nearly double type I and IIA fiber content and nearly half of type IIB fiber content when compared to the M-Vertical and F-Vertical groups.…”
Section: Discussionsupporting
confidence: 88%
“…Relatively larger muscle fibers were observed on the surface of the F-Parallel group, regardless of muscle fiber types owing to the elongated cylindrical shape of the muscle fibers [ 20 , 21 ]. Among the muscle fiber types, IIB or IIX fibers are generally observed to be larger than types I or IIA, regardless of species and breeds [ 19 , 22 , 23 ]. Our results, regardless of cut groups, corroborated with the previous observations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10-μm-thickness sections were obtained by making parallel cuts to the chop surface of M-Vertical group and by making vertical cuts to the muscle fiber orientation of F-Vertical group, respectively, using a cryostat microtome (CM1520, Leica Biosystem, Wtezlar, Germany). The method by Song et al (2020) with some modifications was used to stain the cross-sections and muscle fiber typing. Briefly, each section was incubated with monoclonal anti-myosin heavy chain (MHC) antibodies purchased from DSHB (Iowa, IA, USA), such as BA-F8 (anti-MHC slow/I), SC-71 (anti-MHCs 2a and 2x), BF-35 (anti-MHCs slow/I and 2a), and BF-F3 (anti-MHC 2b).…”
Section: Methodsmentioning
confidence: 99%
“…The method bySong et al (2020) with some modifications was used to stain the crosssections and muscle fiber typing. Briefly, each section was incubated with monoclonal antimyosin heavy chain (MHC) antibodies purchased from DSHB (Iowa City, IA, USA), such as BA-F8 (anti-MHC slow/I), SC-71 (anti-MHCs 2a and 2x), BF-35 (anti-MHCs slow/I and 2a), and BF-F3 (anti-MHC 2b).…”
mentioning
confidence: 99%